The Beneficial Effects of Valproic Acid in Thyroid Cancer Are Mediated through Promoting Redifferentiation and Reducing Stemness Level: An In Vitro Study. (15th May 2014) - Haghpanah, Vahid; Malehmir, Mohsen; Larijani, Bagher; Ahmadian, Shahin; Alimoghaddam, Kamran; Heshmat, Ramin; Ghavamzadeh, Ardeshir; Adabi, Khadijeh; Ghaffari, Seyed H.
Abstract : Valproic acid (VPA) has been identified as a histone deacetylase inhibitor, inducing differentiation in transformed cells. However, no study has shown the effect of VPA in the redifferentiation induction and stemness of anaplastic thyroid. The main objective of this study was to evaluate the efficacy of VPA as a differentiation therapy agent in human thyroid cancer based on its effect on stemness and differentiation process. Indications for differentiation of 8305C and B-CPAP cell lines following VPA treatment were obtained by analyzing cell proliferation rate, morphological changes, adherent-dependent colony formation, and Hoechst 33342 staining. The expressions of stemness, differentiation, and aggressiveness specific marker genes were measured by quantitative RT-PCR. VPA treatment effectively showed growth inhibition in both cell lines. The high nuclear-cytoplasmic (N : C) ratio of 8305C cells markedly decreased and treated cells became more epithelial-like. Treated cells showed stronger Hoechst 33342 fluorescence compared with control cells. The hTERT and OCT-4 reduction was paralleled with adherent-dependent colony formation decrement in both cell lines. VPA effectively induced NIS and TTF-1 in anaplastic cells, it whereas showed no clear pattern in papillary cell line. VPA treatment also resulted in the reduction of MMP-2 and MMP-9. These finding suggest that VPA could redifferentiate the anaplastic thyroid cancer cells.